1968
DOI: 10.1099/00221287-54-1-155
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Mycoplasma mycoides Thread-phase Growth

Abstract: SUMMARYExamination of threads of Mycoplasma mycoides var. mycoides by optical and electron microscopy revealed organisms within a homogeneous mucinous matrix. This matrix stained with the periodic acid-Schiff (PAS) reagent method was almost electron-transparent and was probably lipo-polysaccharide (galactan) material. Treatment of threads with specific antibody produced a clearly visible microscopic precipitate strongly outlining the threads. By electron microscopy this precipitate was electron-dense, homogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1971
1971
2010
2010

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…A capsule staining with RR similar to that demonstrated in the present work has been shown in various mycoplasmas (1,13,14,20,28). It has been suggested that the capsule was associated with the adhesive properties (13,28) or virulence of mycoplasmas (12,14). The relationship between the RR-positive capsule and the radiating fibrils or a fuzzy layer seen on the mycoplasma cells not treated with RR remains to be determined.…”
Section: Discussionsupporting
confidence: 84%
“…A capsule staining with RR similar to that demonstrated in the present work has been shown in various mycoplasmas (1,13,14,20,28). It has been suggested that the capsule was associated with the adhesive properties (13,28) or virulence of mycoplasmas (12,14). The relationship between the RR-positive capsule and the radiating fibrils or a fuzzy layer seen on the mycoplasma cells not treated with RR remains to be determined.…”
Section: Discussionsupporting
confidence: 84%
“…Capsules have been suggested for several species of Mycoplasma in addition to M. mycoides ssp. mycoides (Gourlay and Thrower, 1968). Examples include Mycoplasma dispar (Almeida and Rosenbusch, 1991), M. gallisepticum (Chu and Horne, 1968), M. hyopneumoniae (Tajima and Yagihashi, 1982), M. penetrans (Neyrolles et al, 1998), M. pneumoniae (Wilson and Collier, 1976) and M. synoviae (Ajufo and Whithear, 1978), based mainly on electron microscopy and cationic staining using ruthenium red (Almeida and Rosenbusch, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ultrastructural characteristics of the ibex isolate, evaluated by electron microscopy, showed typical architecture of Mollicutes. Fine granulations were evident on the cell surface, corresponding to a ''slime layer'' made of galactan, known to be present on the surface of Mycoplasma mycoides cluster cells (Gourlay and Thrower, 1968). Despite these indications that the IKC was caused by a Mycoplasma species further work was required to identify it to subspecies level.…”
Section: Discussionmentioning
confidence: 99%